Perceptions of Digital Competency among Student Teachers: Contributing to the Development of Student Teachers' Instructional Self-Efficacy in Technology-Rich Classrooms - Eyvind Elstad; Knut-Andreas Christophersen (MDPI AG, 2017)
Adequate self-efficacy is useful for motivating individuals to engage in continued improvement. This study explores the potential antecedents of instructional self-efficacy beliefs among Norwegian student teachers attending a programme for secondary school teachers. The most important finding was the strong association between the student teachers' perceptions of digital competency to resolve challenges relating to information and communication technology (ICT) in schools and their instructional self-efficacy, which was explored via two dimensions: (1) self-efficacy for maintaining discipline and (2) self-efficacy for influencing students' use of ICT in the service of learning. Implications for practice are discussed. We argue that digital competency among student teachers is important for sustaining instructional self-efficacy in technology-rich classrooms.